El subsector financiero de la economía popular y solidaria y su incidencia en el desarrollo de las PYMES en el cantón Guayaquil, provincia del Guayas período 2015-2017 - Castro Córdova, Marcela Nathali (2019)
The following research work has as final goal to know how the Financial Subsector of the Popular and Solidarity Economy has affected the economic development of SMEs in the Guayaquil canton from 2015 to 2017. to statistical data provided by government websites such as the National Institute of Statistics and Census (INEC), Superintendence of Popular and Solidarity Economy (SEPS) and thanks to the results obtained at the time of conducting surveys that were directed for SMEs and for Cooperatives of Savings and Credit, it was possible to obtain first-hand information on relevant data for the development of this research project………..